If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -5 = (x + 1) Reorder the terms: -5 + 3x = (x + 1) Reorder the terms: -5 + 3x = (1 + x) Remove parenthesis around (1 + x) -5 + 3x = 1 + x Solving -5 + 3x = 1 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -5 + 3x + -1x = 1 + x + -1x Combine like terms: 3x + -1x = 2x -5 + 2x = 1 + x + -1x Combine like terms: x + -1x = 0 -5 + 2x = 1 + 0 -5 + 2x = 1 Add '5' to each side of the equation. -5 + 5 + 2x = 1 + 5 Combine like terms: -5 + 5 = 0 0 + 2x = 1 + 5 2x = 1 + 5 Combine like terms: 1 + 5 = 6 2x = 6 Divide each side by '2'. x = 3 Simplifying x = 3
| 5y+3-1xy=2x+8y-5 | | -7x+9=-40 | | (4_11/4:19/16).(_155/8)= | | 3x+9=-40 | | 87-2x=43x+22 | | 5(w-3)=w-11 | | P=3n | | 5p=6p+12 | | 62-3x=8x+15 | | 19a-7-17a+23=-14 | | 14=7x+4-5x | | 5x+9=58x-2 | | 5-0.03x=0.2-0.05x | | 2n-11+2n-11+n=18 | | 2-3m=m | | y=4x-31 | | 7x+10=8x+5 | | -6y+x=8 | | 15y-8-15y=17 | | -6x-5y=8 | | -3b=11 | | x-3/(x/4)-(4/x) | | x-3/((x/4)-(4/x)) | | (x^2/20+x/4+1/5)=0 | | f=11/(5)2 | | 8x=24x^2 | | 4y^2-27y+147=0 | | 4(x-7)=24 | | 5p+7q=71 | | 8+(8)/(x-5) | | 3f-4=20 | | 5/1*3/4 |